Study on the temperature dependence of pitting behaviour of AISI 4135 steel in marine splash zone - Yu, X.; Huang, Y.; Yadav, A.; Qu, W.; De Marco, Roland (Electrochemical Society of Japan, 2015)
© The Electrochemical Society of Japan, All rights reserved. The corrosive condition at marine splash zone is detrimental to steel structures of offshore applications. The corrosion at splash zone is the most serious not only for uniformed corrosion but also localized corrosion. Practically, marine structures experience cyclic seasonal temperature change. Temperature acts as an important factor affecting corrosion process. In this paper, the effects of temperature on pitting behavior of a low alloy high strength steel (AISI 4135) in marine splash zone have been investigated using electrochemical techniques and morphology observations. The area of hysteresis loop was greater under seawater film at lower temperatures than that at high temperatures, indicating that the pitting corrosion sensitivity is high at lower temperature. AISI 4135 steel has the potential danger of pitting corrosion in marine splash zone after long exposure.